Association between symptom severity and internal capsule volume in obsessive-compulsive disorder - Duran, Fabio Luis de Souza; Hoexter, Marcelo Queiroz; Valente, Antonio Augusto; Miguel, Euripedes Constantino; Busatto, Geraldo Filho (Neuroscience letters, 2009)
Neurobiological models support an involvement of white matter tracts in the pathophysiology of obsessive-compulsive disorder (OCD), but there has been little systematic evaluation of white matter volumes in OCD using magnetic resonance imaging (MRI). We investigated potential differences in the volume of the cingulum bundle (CB) and anterior limb of internal capsule (ALIC) in OCD patients ( n = 19) relative to asymptomatic control subjects ( n = 15). White matter volumes were assessed using a 1.5T MRI scanner. Between-group comparisons were carried out after spatial normalization and image segmentation using optimized voxel-based morphometry. Correlations between regional white matter volumes in OCD subjects and symptom severity ratings were also investigated. We found significant global white matter reductions in OCD patients compared to control subjects. The voxel-based search for regional abnormalities (with covariance for total white matter volumes) showed no specific white matter volume deficits in brain portions predicted a priori to be affected in OCD (CB and ALIC). However, large clusters of significant positive correlation with OCD severity scores were found bilaterally on the ALIC. These findings provide evidence of OCD-related ALIC abnormalities and suggest a connectivity dysfunction within frontal-striatal-thalamic-cortical circuits. Further studies are warranted to better define the role of such white matter alterations in the pathophysiology of OCD, and may provide clues for a more effectively targeting of neurosurgical treatments for OCD.